Intervenção psicoeducativa e parâmetros imunológicos em pacientes HIV+ - Amaral, Jodi Dee Hunt Ferreira do (2001)
This study was designed to observe the effect of a psychoeducational intervention on CD4/CD8 and viral loads in the HIV+ patients as well as to promote a space where patients could learn more about the HIV virus and direct their attention to aspects that need to be dealt with for their well-being. This study was also undertaken to evaluate the prognostic value of IL-16 serum levels, in comparison to CD4 counts, CD8 counts, viral load and 02 microglobulin levels (J32-MG). Two groups of HIV+ patients, one of women infected heterosexually (n=7) and another of male homo/bisexuals (n=11) participated in psychoeducational encounters. Blood samples were drawn at baseline (T1), approximately 3 months after baseline and immediately after group intervention (T2) and approximately 6 months after baseline (T3) to perform CD4/CD8 and viral load exams. Laboratory data from 55 HIV-infected subjects and 10 AIDS inpatients were analyzed to compare prognostic values. Encounters were reported as informative. General study results revealed that patients who attended less than 7 sessions had significantly lower CD4 numbers, between T1 and T3 ( p = 0.0039), patients who attended more than 7 sessions had significantly lower viral loads between T2 and e T3 ( p = 0.0234). Patients who were not offered any session had stable CD4 counts and viral loads over study period. The median values, in general, did not differ neither according to clinical classification nor to time (in months) of patients' diagnosis. An inverse correlation was detected between 1L-16 levels and viral load (r =-.269) and between 02-MG and CD4 (r =-610) while a positive correlation was observed between 132-MG and viral load (r = 0.433). Three conclusions may be stated. In relation to the psychoeducational intervention and immunological parameters, a larger number of participants is needed for significant statistical analysis. This study is favorable to the adoption of j32-MG, as a more useful predictor than 1L-16 levels for AIDS progression. Athough, 1L-16 is not confirmed as an useful marker in I IIV infection it still warrants future studies especially in regard to its feasibility as a therapeutic weapon.